Relationship Between Lactic Acid Levels And Work Fatigue In Palm Oil Harvesters At PT. X Kampar Regency - Yuharika Pratiwi; Dinda Queenty Dzakiyah Hartono; Ruswaldi Munir (Lembaga Pengembangan Kinerja Dosen, 2024)
Work fatigue is a condition caused by physical and mental activities that exceed capacity. According to National Safety Council data, > 60% of work accidents are caused by fatigue. In Indonesia, the agriculture, fisheries, plantation, and forestry sectors occupy the second position in the cause of work accidents. Work fatigue can be caused by both internal and external factors. Fatigue caused by external factors causes changes in the body's biochemical processes so that lactic acid builds up in the muscles. Initial survey on PT. X is located in Kampar Regency, information was obtained that there were cases of work accidents in harvesters which were mostly caused by work fatigue. Objective To determine the relationship between lactic acid levels and work fatigue in palm oil workers in PT. X Kampar Regency Methods This study was conducted using observational analytical methods, cross sectional research design. The sampling technique uses total sampling, as many as 114 samples have met the inclusion criteria. Bivariate analysis uses the Spearman test. Result p-value = 0.000; r = 0.607 with strong correlation strength and positive direction Conclusion There is a relationship between lactic acid levels and physical fatigue in harvesters